From Lab to Zoom: Adapting Training Study Methodologies to Remote Conditions - Bambha, Valerie P.; Casasola, Marianella (Frontiers in Psychology, 2021)
Training studies extend developmental research beyond single-session lab tasks by evaluating how particular experiences influence developmental changes over time. This methodology is highly interactive and typically requires experimenters to have easy, in-person access to large groups of children. When constraints were placed on in-person data collection due to the COVID-19 pandemic, administering this study format in the conventional manner became unfeasible. To implement this type of research, we devised an alternative approach that enabled us to conduct a live, multi-session training study using a diverse array of activities through an online interface, a task necessitating creative problem-solving since most existing remote methodologies either rely on unsupervised methods or have been limited to single sessions and restricted to a limited number of tasks. The current paper describes the technological and practical adaptations implemented in our online training study of 118 4- and 5-year-old children. An experimenter interacted with the children once a week for five weeks over Zoom. The first and final sessions were dedicated to collecting baseline and post-test measures, while the intermediate three weeks were structured as a training designed to teach children specific spatial-cognitive and fine motor skills. The assessments and training contained image-filled spatial tasks that experimenters shared on their screen, a series of hands-on activities that children completed on their own device and on paper while following experimenters’ on-screen demonstrations, and tasks requiring verbal indicators from the parent about their child’s response. The remote nature of the study presented a unique set of benefits and limitations that has the potential to inform future virtual child research, as our study used remote behavioral methods to test spatial and fine motor skills that have typically only been assessed in lab settings. Results are discussed in relation to in-lab studies to establish the viability of testing these skills virtually. Because recruitment in this study was not limited by location, it was possible to obtain a large, geographically diverse sample. As our design entailed continual management of communication issues among researchers, parents, and child participants, strategies for streamlined researcher training, diverse online recruitment, and stimuli creation are also discussed.